The handbook on optical constants of semiconductors in tables and figures - Adachi, Sadao (World Scientific, 2012)
Knowledge of the refractive indices and absorption coefficients of semiconductors is especially important in the design and analysis of optical and photonic devices. This book presents data on the optical constants of various elemental and compound semiconductors. A complete set of the optical constants of the semiconductors are presented in tabular and graphical forms over the entire photon-energy range. They are: the complex dielectric constant e(E)=e1(E)+ie2(E), the complex refractive index n*(E)=n(E)+ik(E), the absorption coefficient a(E), and the normal-incidence reflectivity R(E).